Tropes at Play in Latour’s Work. A Tensive Semiotic Portrait of Modernity as a Semiosphere - Tassinari, Carlo Andrea (E|C, 2023)
The semiotic interpretation of Bruno Latour s work often focuses on the syntactic models he borrowed from semiotics. In this paper, I shift the attention towards the underlying semantic models of Latour s work. This shift does not claim any philological intentions; its objective is primarily theoretical. My aim is to establish a connection between Lotman's perspective on rhetoricity, which is a fu ndamental mechanism of meaning making in the semiosphere, Latour's anthropological and experimental exploration in his Inquiry into Modes of Existence , and the tensive semiotic concept of "enunciative practice". In our view, bridging the gap between these research projects enables semiotics of culture to align itself with contemporary anthropology as a leading human science, providing a more heuristic articulation of Latour's Inquiry.